Faculty perceptions of the CORETXTPLUS® paradigm - Abendschein, Alex (Kansas State University, 2012)
This master’s report is a study of current textbook trends within higher education. The report looks at multiple methods of textbook delivery for faculty members within the higher education community. The report further investigates a new textbook paradigm created by faculty members at the University of Wisconsin Oshkosh. The author of this report has spent several years researching textbook trends and has presented on this topic on several occasions. By analyzing some qualitative data collected at the University of Wisconsin Oshkosh, the author will provide a partial evaluation of the CoreTxtPlus® paradigm and offer suggestions to future faculty members looking for an innovative way to provide course content to their students.
Keywords: Textbooks; Teaching Methodologies; CORETXTPLUS; E-Books; Textbook Formats; Teaching Paradigms; Curriculum Development (0727); Education, Technology (0710); Higher Education (0745)